2021
DOI: 10.1371/journal.pone.0248157
|View full text |Cite
|
Sign up to set email alerts
|

Understanding variations and influencing factors on length of stay for T2DM patients based on a multilevel model

Abstract: Aim Shortening the length of stay (LOS) is a potential and sustainable way to relieve the pressure that type 2 diabetes mellitus (T2DM) patients placed on the public health system. Method Multi-stage random sampling was used to obtain qualified hospitals and electronic medical records for patients discharged with T2DM in 2018. A box-cox transformation was adopted to normalize LOS. Multilevel model was used to verify hospital cluster effect on LOS variations and screen potential factors for LOS variations fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…It is also plausible that the suicide attempt group was more likely to have psychological symptoms compared with the no suicide attempt group, the presence of which is known to be associated with prolonged hospital stay [38,39]. Previous studies have reported that prolonging hospital LOS occupies beds and caregivers for a longer time, as well as increasing healthcare costs and economic burden [40,41]. The excess length of hospital stay is also known to be associated with increased complications, such as hospital-acquired infections [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…It is also plausible that the suicide attempt group was more likely to have psychological symptoms compared with the no suicide attempt group, the presence of which is known to be associated with prolonged hospital stay [38,39]. Previous studies have reported that prolonging hospital LOS occupies beds and caregivers for a longer time, as well as increasing healthcare costs and economic burden [40,41]. The excess length of hospital stay is also known to be associated with increased complications, such as hospital-acquired infections [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…If in-hospital psychiatric consultation becomes less available, it is likely to result in increased psychiatric hospital transfers and emergency ward LOS. Prolonging hospital LOS occupies beds and caregivers for a longer time, increases healthcare costs and economic burden, [35,36] and increases complications unrelated to admission diagnosis, such as hospital-acquired infections. [37,38] A shortage of psychiatric services is a ubiquitous problem in Japanese EDs, [7] despite the increasing number of ED presentations of patients with psychiatric illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…( Hou et al, 2020 ; Hu, 2020 ; Mohapatra, Rajaram & Mallick, 2018 ), there were limited studies on the length of hospital stay and medical expenses on these patients. In general, the length of hospital stay can be influenced by many factors, such as baseline demographics, underlying comorbidities, disease complications, and medical expenses ( Chen et al, 2017 ; Liu et al, 2021 ). Prolonged length of hospital stay has been associated with high medical expenses, cognitive impairment, functional dependence, and high comorbidity ( Bo et al, 2016 ; Kamitani et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%